The relationship between artificial intelligence (AI) and its aspects in higher education - Razia, Bahaa; Awwad, Bahaa; Taqi, Najma (Development and learning in organizations, 2023)
Purpose This paper aims to provide better understanding on this phenomenon, as well as some recommendations to assist in preparing Al technology and its related aspects during crisis like Covid period and beyond. Design/methodology/approach The study consisted of two phases. Phase one focused on identifying top higher education institutions according to the QS world university ranking. As a result, 180 higher education institutions in the Arab region were found, with the 2022 QS Arab region university ranking. The study selected top 20 performing institutions. Each institution has been assessed according to six metrics including: international student ratio, international research network, international ration, Web impact, citation per page and paper per faculty. Phase two explored the adapted Al applications and their related aspects that are used in each institution using a learning online questionnaire. Pilot tests were used to determine the validity and reliability of the measures. Findings Numerous factors that lead to enhancing high education using Artificial Intelligence in higher education institutions have emerged from this study. These factors include; knowledge management, trust, learning, technical resources and complexity. First, effective knowledge management assists in maintaining information in a place where it is easy to share and access. Second, trust is considered a critical factor in dealing with uncertainties like covid-19. It needs to be effectively addressed by students and staff members, especially in higher education. Without trust, decisions cannot be successfully made and actions may be delayed or stalled. Third, continuous learning is a key factor that tends to enhance the capability of dealing with new routines or potential challenges. Fourth, technical resources refer to electronic devices and tools that are used by students and academics to interact and share knowledge. Originality/value Students and faculty academics perceive things and use Al technology differently, which can lead to misunderstanding and create tension between them. Many higher education institutions have adapted great Al technology applications, but they are significantly less proficient than previously thought at understanding how to leverage this technology to produce helpful solutions to their business difficulties.